Dead silence - Hoffman, Gregg; Koules, Oren; Burg, Mark; Wan, James; Universal Pictures (Universal City, CA : Universal Studios Home Entertainment, 2007)
After receiving a strange package with the doll named Billy, Jamie's wife is murdered. Destined to find out the truth, Jamie goes to the town of Raven's Fair where the ventriloquist Mary Shaw used to perform and is buried. After she went mad in the 1940s, Mary was accused of kidnapping a young boy who yelled out in one of her performances that she was a fraud. Because of this she was hunted down by townspeople, who in the ultimate act of revenge, cut out her tongue and then killed her. They buried her along with her'children,' a handmade collection of vaudeville dolls, and assumed they had silenced her forever
Title from title screen
Screenplay by Leigh Whannell ; director of photography, John R. Leonetti ; editor, Michael N. Knue ; music, Charlie Clouser ; costume designer, Denise Cronenberg ; production designer, Julie Berghoff
Cast: Ryan Kwanten, Amber Valletta, Donnie Wahlberg, Michael Fairman, Joan Heney, Bob Gunton, Laura Regan, Dmitry Chepovetsky, Judith Roberts, Keir Gilchrist, Steven Taylor, David Talbot, Steve Adams, Shelley Peterson
DVD Format
Dolby digital
In English, Japanese or Thai with optional English, Japanese, Thai, Korean, Indonesian, Cantonese or Mandarin Traditional subtitles
Keywords: Ventriloquists -- Drama; Murder -- Investigation -- Drama; Revenge -- Drama; Kidnapping -- Drama